Effects of a ball-backrest chair on the muscles associated with upper crossed syndrome when working at a VDT. - Yoo W; Yi C; Kim M (Work, 2007)
This study examined the effect of a ball-backrest chair on the weakness and tightness of muscles associated with upper crossed syndrome when working at a visual display terminal (VDT). The surface electromyography (EMG) was recorded from the serratus anterior, middle trapezius, and upper trapezius muscles of 20 adults as they performed VDT work, which are known as the weakened and tightened muscles of upper crossed syndrome. The recorded signals were averaged and normalized to the mean amplitude of the EMG signal obtained during submaximal reference voluntary contractions. The significance of differences between the use of a general-purpose backrest and a ball backrest was tested by paired t-test, with the significance cutoff set at [alpha]=0.05. The activities of the serratus anterior and middle trapezius muscles increased and that of the upper trapezius muscle decreased when sitting in a ball-backrest chair compared to when sitting in a chair with a general-purpose backrest (p<0.05). These results indicate that the use of a ball-backrest chair reduces the risk of patients with upper crossed syndrome developing muscles soreness or injury related to overuse when working at a VDT.